GLOBAL DIVERSITY AS A BASIS OF ADAPTIVE OAT BREEDING - G. A. Batalova (Труды по прикладной ботанике, генетике и селекции)
Competitive varieties of covered and naked oats resistant and/or tolerant to region-specific ecological factors limiting their productivity have been developed by selection and hybridization techniques using the germplasm from VIR’s oat collection. Among them there are oats varieties widely cultivated in Russia, such as Argamak, Krechet and Gunter, and new varieties Sapsan and Avatar combining high productivity (8-11.2 t/ha) with resistanceto biotic and abiotic stressors. From 250 up to 350 oat samples are evaluated annually in parallel collection nurseries on two cultivated (Kirov and Falenki) and one naturally acidified (Falenki, 13.45-17.23 mg-equiv. Al3 +/100 g of soil) plots of soddy-podzolic soils. It is shown that expanding the spectrum of recombinations requires development of mixedhybrids on the basis of covered and naked genotypes. Thus, using covered and naked source materials in crossings, the naked oat cultivar Persheron has been released and included in the State Register of Breeding Achievements of the Russian Federation since 2013; and the covered oat cultivar Medved with high grain quality has been submitted to the State Crop Variety Trials.